Influence of Prolonged Storage Process, Pasteurization, and Heat Treatment on Biologically-active Human Milk Proteins - Jih-Chin Chang; Chao-Huei Chen; Li-Jung Fang; Chi-Ren Tsai; Yu-Chuan Chang; Teh-Ming Wang (Pediatrics and Neonatology)
The bioactive proteins in human milk may be influenced by prolonged storage process, pasteurization, and heat treatment. This study was conducted to evaluate the effects of these procedures. Materials and methods: Three forms of human milk – freshly expressed, frozen at −20°C for a prolonged duration, and pasteurized milk – were collected from 14 healthy lactating mothers and a milk bank. The concentrations of major bioactive proteins (secretory immunoglobulin A, lactoferrin, lysozyme, and leptin) were quantified using enzyme-linked immunosorbent assay kits. Changes in these proteins by heat treatment at 40°C or 60°C for 30 minutes were further evaluated. Results: The mean concentrations of lactoferrin and secretory immunoglobulin A were significantly reduced by 66% and 25.9%, respectively, in pasteurized milk compared with those in freshly-expressed milk. Heat treatment at 40°C or 60°C did not cause significant changes in lactoferrin and secretory immunoglobulin A, but there was an apparent increase in lysozyme (p = 0.016). There were no significant differences in leptin level among these three forms of milk prior to (p = 0.153) or after heat treatment (p = 0.053). Conclusion: Various freezing/heating/pasteurization processes applied to human milk prior to delivery to neonates could affect the concentration of immunomodulatory proteins, especially lactoferrin, secretory immunoglobulin A, and lysozyme. Leptin was unaffected by the various handling processes tested. Fresh milk was found to be the best food for neonates. Further studies are warranted to evaluate the functional activity of these proteins and their effects on infants' immunological status.